Characterization of rabbit meat marinated in mustard and white wine with spices - González Balmaceda, Felipe (2023)
Introduction. Developing new commercial options can bring benefits to the rabbit meat market. Objective. To evaluate the sensory, physicochemical, and microbiological characteristics of two marinated rabbit meat preparations in mustard and white wine with spices. Materials and methods. The research, conducted in Costa Rica in 2016, involved a refrigeration storage study with two marinated rabbit meat products: one with mustard and the other with wine and spices. A total count of anaerobic psychotrophs, yield, color, pH, texture, and sensory satisfaction was evaluated with a panel of 100 consumers. Results. There were no significant differences (p>0.05) in yield. Lower pH values were obtained than those reported in fresh rabbit meat for the wine preparation, which had lower counts of anaerobic psychotrophs (p>0.05), proving greater stability and allowing storage for up to 28 days without exceeding 106 CFU/g. A high L* value was obtained for both preparations. Significant differences were found in all color parameters according to the preparation method (p<0.05), and for L*, b*, and C, there was an interaction between the factors of time and marination. The texture did not show differences (p>0.05) based on the marination, but there were differences between this method and time for shear force, hardness, chewiness, and elasticity. The preparation did not affect the texture parameters compared to non-marinated rabbit meat. Both preparations had good sensory acceptance. Conclusion. The marinating processes with mustard and wine with spices generated products with high sensory acceptance and desirable physicochemical and microbiological characteristics.